A Psychological Analysis of The Main Character in “Regret” Short Story by Kate Chopin - Suker, Gede Andrian; Mulyana, Novita (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2024)
This qualitative research aims to analyze psychological aspect of human motivation of the main character in “Regret” short story. The story is about Mamzelle Aurlie, fifty years old women, who refused to get married, and enjoy to live solitaire. However, she later feels pleasant for the first time on taking care her neighbor’s children. The theory of psychology of human motivation by Bernhardt (1953) were used to analyze the data that already collected using documentation method. The result found out that Mamzelle showed all aspect from theory, namely appetites (11.11%), wants (22.22%), emotion (33.33%), feeling and attitude (11.11%), also social motives (22.22%). Emotion lead as the most occurrence in the finding analysis. One of the iconic aspects that must be highlighted, which is the climax of the story, is regarding to Mamzelle’s emotion of regret when the children’s away, making her lonely.